Knights and castles - Rutland, Jonathan; Berry, John (New York : Random House, 1987)
Describes the history, structure, and functions of medieval castles and the equipment and activities of knights in the Middle Ages.
Includes index.
Keywords: Knights and knighthood -- Juvenile literature; Castles -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Castles; Knights and knighthood; Civilization, Medieval; Castles; Knights and knighthood; Medieval civilization